2212. Preliminary Screening Results Outside the 1945–1965 Birth Cohort: A Forgotten Population for HCV?. (26th November 2018) - Winetsky, Daniel; Slowikowski, Jacek; Zucker, Jason; Scherer, Matthew; Gordon, Peter
Abstract: Background: Historically, hepatitis C virus (HCV) infection was most prevalent among those born between 1945 and 1965. Current CDC guidelines recommend screening for HCV only among this birth cohort or in patients with known risk factors for HCV infection. However, recent epidemiologic data shows increasing HCV incidence among younger patients. Universal screening may facilitate earlier recognition of infected individuals. Methods: At our center, the admission order set previously included a required prompt to order HCV screening for patients born between 1945 and 1965. In December 2017, we expanded the default order to include all patients above the age of 18. We compared rates of HCV screening and positivity during the first three months of this policy to similar months in the preceding year. We also reviewed the charts of HCV-positive patients to identify documented risk factors. Results: From December 2017 to February 2018, a total of 11, 118 patients were screened with 389 (3.5%) positive results, compared with 8, 423 patients and 361 (4.3%) positives during the same months in 2016–2017. Outside the birth cohorts, 179 (1.1%) patients were HCV positive in 2017–2018 compared with 117 (2.3%) in 2016–2017. Thirty-five HCV-positive patients were born outside the birth cohort. Twenty-one (60%) had no documented risk factors. Among the cohort born after 1965, only three out of 17 (17%) patients had no known risk factors, compared with all 18 (100%) patients born before 1945. Conclusion: Documented substance use disorders and social vulnerability were highly prevalent in HCV-positive patients born after 1965 and rare in those born before 1945. Disclosures: All authors: No reported disclosures.